Natural resource management and resource rights for agriculture - Place, Frank; Meinzen-Dick, Ruth S.; Ghebru, Hosaena (International Food Policy Research Institute, 2021)
For the foreseeable future, agriculture in developing countries will be overwhelmingly based on farming that is dependent on natural resources to produce edible plants, provide feed for livestock, or to raise fish. The abundance of natural resources affects total agricultural production but the health, state, or quality of natural resources affects both total production and productivity of agriculture. Productivity growth in agriculture is of paramount importance for feeding growing populations in a world with limited natural resources (FAO 2012b). However, achieving high productivity is not easily accomplished in smallholder-dominant countries as evidenced by high yield gaps—the difference between actual and potential yields—in much of the developing world (FAO 2011) and productivity gaps between agriculture and other sectors (Gollin, Lagakos, and Waugh 2014). Obtaining high productivity in a way that sustainably uses natural resources is even more elusive globally.